2017
DOI: 10.1111/liv.13293
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C: efficacy and safety in real life

Abstract: Interferon-free combinations were registered in 2014 and 2015 for the treatment of chronic HCV infection. As a result, real-world experience has been gathered in the last year and this paper presents data available in September 2016. Real-world studies on the efficacy of the ledipasvir/sofosbuvir (LDV/SOF)±ribavirin (RBV) regimen showed a sustained virologic response (SVR) rate of between 91% and 98%. The SVR rate in the 13858 patients included in this paper was 94%, and 92% in the 3506 patients with cirrhosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 49 publications
6
34
1
2
Order By: Relevance
“…A recent review on efficacy and safety of oral DAA reported an overall SVR12 of 92% in cirrhosis patients treated with sofosbuvir/ledipasvir combination therapy . Other real‐life observational studies have reported an SVR12 between 94% and 98% in treatment‐naïve genotype 1 patients treated with combination of sofosbuvir and ledipasvir; including a study by Zeng et al, wherein naïve genotype 1 patients were treated with a combination of generic sofosbuvir and ledipasvir, SVR12 among cirrhotic and noncirrhotic patients was 96.8% and 96.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review on efficacy and safety of oral DAA reported an overall SVR12 of 92% in cirrhosis patients treated with sofosbuvir/ledipasvir combination therapy . Other real‐life observational studies have reported an SVR12 between 94% and 98% in treatment‐naïve genotype 1 patients treated with combination of sofosbuvir and ledipasvir; including a study by Zeng et al, wherein naïve genotype 1 patients were treated with a combination of generic sofosbuvir and ledipasvir, SVR12 among cirrhotic and noncirrhotic patients was 96.8% and 96.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) is a leading cause of advanced liver disease and thus a public health problem worldwide . Second‐generation direct‐acting antivirals (DAAs) have been shown to dramatically improve HCV eradication, a result that has been confirmed by real‐life studies …”
Section: Introductionmentioning
confidence: 96%
“…The combinations of DAAs were designed to target HCV NS3/4A protease, NS5B polymerase and NS5A and have resulted in a revolution in the treatment of chronic hepatitis C. Interestingly, even in difficult to treat patients with HIV co‐infection, compensated and decompensated cirrhosis, liver transplantation and severe renal impairment, these combinations show high efficacy (90%‐100% rates of SVR) and excellent safety. Results of their efficacy and safety in real life studies are in accordance with those of clinical trials and show SVR rates of more than 90% in patients with genotypes 1 and 4 …”
Section: Hcvmentioning
confidence: 60%